Plant host selection for spore production of Glomas mosseae - Deewatthanawong, R.; Bannajit, W.; Deewatthanawong, P.; Bunya-Atichart, K. (My University, 2022)
Five species including Ipomoea aquatica, Triticum aestivum, Oryza sativa, Zea mays, and Vigna radiata were used as plant hosts for spore production of Glomas mosseae. Seeds of all plant species were surface sterilized and grown in sterilized growing medium with a ratio of 1 part soil to 8 part sand. Each pot of each plant species was inoculated with 30 spores of G. mosseae and compared with the control without inoculum. Each treatment consisted of five replicates containing four pots. Half-strength Hoagland solution was applied once a week and plant growth parameters including diameter, height, and number of leaves were recorded every week for 2 months. Spores of G. mosseae in the rhizosphere, root colonization, and plant dry mass were measured after 2 months of inoculation. Results showed that G. mosseae improved plant growth of all plant species, with maximum increase in plant diameter found in Z. mays; while, maximum effects on plant height and root dry mass were observed in V. radiata. Results of spore formation suggested Z. mays as the most suitable host for mass spore production with the highest spore numbers of 97.4 100 g-1 soil; however, no significant differences in root colonization were shown among the five plant species.
Keywords: host preference; mass spore production; mycorrhizal fungi; pot culture